Relative frequency of hepatitis B virus, human papilloma virus, Epstein-Barr virus, and herpes simplex viruses in the semen of fertile and infertile men in Shiraz, Iran: A cross-sectional study - Hossein Afrakhteh; Negar Joharinia; Akhtar Momen; Razieh Dowran; Abouzar Babaei; Parisa Namdari; Mohammad Motamedifar; Bahia Namavar Jahromi; Jamal Sarvari (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: About 8-12% of couples on reproductive age suffers from infertility worldwide. Since 1993, the role of genital tract infections by microbes, including viruses that can infect the sperm, in human infertility has been proposed. Objective: To investigate the frequency of hepatitis B virus (HBV), human papilloma virus (HPV), Epstein-Barr virus (EBV), and herpes simplex virus (HSV) infection in the semen of fertile and infertile men referred to the Mother and Child Hospital, Shiraz, Iran. Materials and Methods: In this cross-sectional study, 350 men including 200 infertile and 150 fertile men were included. All semen samples were allowed to liquefy, followed by the assessment of sperm parameters. DNA was extracted using a DNA extraction kit (CinaGene, Tehran, Iran) according to the manufacturer's instructions. Detection of HBV, HPV, EBV, and HSV1/2 was done by the PCR method. Results: The mean age of the participants was 36 ± 7 yr. Molecular results showed that 16 samples (8%) of infertile men and 5 (3.3%) of fertile men were positive for HBV, which was not statistically significant (p = 0.069). Only one sample of the fertile participants was positive for HPV. None of the semen samples of the infertile or fertile groups was positive for the presence of EBV or HSV1/2. Conclusion: The results of this study indicated that HBV, HPV, EBV, and HSV might not be involved in men's infertility. Further studies are recommended for clarifying the role of these viruses in infertility.